Cell Interaction - Gowder, Sivakumar (IntechOpen, 2012)
The book Cell Interaction focuses on various processes that occur within and outside the cells. Cell interactions are important for functioning of many organ systems: cell adhesion, tissue development, cellular communication, inflammation, tumor metastasis, and microbial infection. Key features include developmental cell interactions, immune and neural cell interactions, cell interactions in normal and disease conditions and advanced level methods to evaluate cell interactions. This book will be a significant resource to all scientists and physicians who are intended to explore more on cells.